Arsitektur misi Perjanjian Lama: Pembacaan kanonik-naratif dari penciptaan hingga tradisi kenabian - Masneno, Denny Folkes (Sekolah Tinggi Teologi Pelita Bangsa, Jakarta, 2026)
Debates over the locus of biblical mission reveal a reductive tendency that positions the Old Testament (OT) as a mere prefiguration of New Testament mission, neglecting the theological coherence that shapes God's people from creation to the prophetic tradition. This study argues that OT theology contains an integral mission structure, not merely isolated motifs such as the proto-evangelium or the Abrahamic promise. Using a canonical-narrative approach and covenant-theology analysis, it traces the progression of OT mission through three nodes: the representational mandate in creation, the formation of missional identity through covenant, and the affirmation and universal expansion through the prophetic tradition. The findings demonstrate that mission functions as a hermeneutical category organizing the narrative; covenantal structures, sending patterns, and prophetic rhetoric consistently orient God's people toward a cross-national representational task. The study concludes that the OT offers an